Transcriptomic Insights into Dual Temperature–Salinity Stress Response in “Shuike No. 1”, a Pioneering Rainbow Trout Strain Bred in China - Xiaojun Liu; Gaochao Wang; Tianqing Huang; Enhui Liu; Wei Gu; Peng Fan; Kaibo Ge; Datian Li; Yunchao Sun; Gefeng Xu (Biology)
Global warming poses a significant threat to aquaculture, particularly for cold-water species like rainbow trout (Oncorhynchus mykiss). Understanding the molecular mechanisms underlying stress responses is crucial for developing resilient strains. This study investigates the dual stress of salinity and temperature response of “Shuike No. 1” (SK), a pioneering commercially bred rainbow trout strain in China, using RNA-sequencing of gill, intestine, and liver tissues from fish exposed to four treatment combinations: freshwater at 16 °C, freshwater at 25 °C, saltwater (30‰) at 16 °C, and saltwater at 25 °C. Differential gene expression analysis identified a substantial number of DEGs, with the liver showing the most pronounced response and a clear synergistic effect observed under combined high-temperature and salinity stress. Weighted gene co-expression network analysis (WGCNA) revealed stress-responsive gene modules and identified hub genes, primarily associated with gene expression, endoplasmic reticulum (ER) function, disease immunity, energy metabolism, and substance transport. Key hub genes included klf9, fkbp5a, fkbp5b, ef2, cirbp, atp1b1, atp1b2, foxi3b, smoc1, and arf1. Functional enrichment analysis confirmed the prominent role of ER stress, particularly the pathway “protein processing in the endoplasmic reticulum.” Our results reveal complex, tissue-specific responses to dual stress, with high temperature exerting a stronger influence than salinity. These findings provide valuable insights into the molecular mechanisms underpinning dual stress responses in SK, informing future breeding programs for enhanced resilience in the face of climate change.